Increase ofstimulant influence remittances from abroad (World of finance, 2019)
Introduction. International migration is accompanied by strong financial flows, which are formed due to money transfers of migrants. Ukraine is one ofthe largest suppliers of labours to the countries of the European Union and other countries and, in accordance with it, it is one of the largest recipients ofremittances.he purpose of this article is to investigate the impact of remittances of citizens from abroad on the socio-economic environment in Ukraine and to develop recommendations for improving theiruse forthe benefit of society as a whole.Results. It’s found out the reasons of the transfer of private money to Ukraine and the main factors influencing their volumes are determined. The dynamics of remittances of private money transfers to Ukraine from abroad is analyzed. It is ascertained that money transfers from Ukrainian migrants are significant, their volumes make up about 6% of GDP. The influence of remittances on the socio-economic development of Ukraine is researched. It is noticed positive and negative consequences for households and the state from remittances. It has been established that remittances are significant additional income of households and are mainly spent on consumption. Their positive impact on gross national income, balance of payments, welfare of the population, poverty level, unemployment rate is argued.Conclusion. In order to use remittances from abroad in the interests of the entire society as a motive for social and economic development, a focused and effective migration policy of the state is needed. One of the most important tasks of the macroeconomic policy of Ukraine should be the creation of such conditions that migrant remittances should be received by official channels and used not only forconsumerpurposes, but also for investing.